Effect of Compensatory Growth on Feedlot Performance of Sudanese Desert Lambs (Journal of Veterinary Medicine and Animal Production, 2021)
The study conducted to detect the effect of compensatory growth on feedlot performance of the Sudanese desert lambs. Twelve lambs (Hamri ecotype) of the same initial weight (23±0.16 kg) were used in this experiment. The animals were randomly divided into two groups: the first group (A) was ad libitum offered a high energy diet (10. 50 MJ/Kg DM) for 8 weeks. While the second group (B) was given a low energy diet (8.03 MJ/Kg DM) throughout the same period. Lambs of the second group were found just to maintain their weight. After that period the lambs from the second group were offered the high energy diet (10. 50 MJ/Kg DM) until they reached the final weight obtained by the first group . It spent 6 weeks to reach that weight. Data were collected daily and weekly for feed consumption and weekly for weight gain. The results showed significant difference in daily live weight gain (P